Total Parathyroidectomy: A Surgical Management for Uncontrolled Secondary Hyperparathyroidism in a Patient with End Stage Renal Disease - Jeanne O. Madrid; Celso V. Ureta (Philippine Journal of Otolaryngology Head and Neck Surgery, 2008)
Objective:  To present the case of an adult patient with end stage renal disease who underwent total parathyroidectomy with autotransplantation for uncontrolled secondary hyperparathyroidism